2008
DOI: 10.1167/iovs.07-0065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photocoagulation on Intraretinal Po2in Cat

Abstract: Previous measurements showed increased Po(2) in the preretinal vitreous of rabbits and pigs (but not cats) after photocoagulation of the outer retina. These intraretinal measurements in cats provide further evidence for a chronic increase in inner retinal Po(2) in lesioned areas during air breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…Anterior segment hypoxia and additional VEGF from the retina will stimulate neovascularisation on the iris. The practice of endophotocoagulation during vitreous surgery helped reduce this threat, as the photocoagulation reduced retinal hypoxia (17,22,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and VEGF production, thus decreasing concentration gradients and transport of both oxygen and VEGF between anterior and posterior segments.…”
Section: Iris Neovascularizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Anterior segment hypoxia and additional VEGF from the retina will stimulate neovascularisation on the iris. The practice of endophotocoagulation during vitreous surgery helped reduce this threat, as the photocoagulation reduced retinal hypoxia (17,22,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and VEGF production, thus decreasing concentration gradients and transport of both oxygen and VEGF between anterior and posterior segments.…”
Section: Iris Neovascularizationmentioning
confidence: 99%
“…4). Naturally, laser photocoagulation will contribute to this by also relieving hypoxia of remaining retinal cells and thus reducing VEGF production (8,17,22,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) Understanding the physiological principles makes it possible to combine treatment modalities in a sensible way (Fig. 5).…”
Section: Retinal Neovascularisationmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 In spite of the fact that laser panretinal photocoagulation for diabetic retinopathy has been used since it was first suggested by Meyer-Schwickerath almost 50 years ago, 22 and that grid laser treatment in the management of macular oedema has been used for some 40 years, 23 some aspects of the mode of action of laser in these and similar conditions remain incompletely explained. Thus, although it has been established both experimentally [24][25][26][27] and clinically [28][29][30][31] that laser treatment results in an increase in oxygen availability in the inner retina, explanations for this finding have varied between an increased inward diffusion of oxygen from the choroid through laser-disrupted tight junctions in the retinal pigment epithelium (RPE), 32 and a reduced oxygen demand in the outer retina (and a consequent increased availability of oxygen in the inner retina) resulting from laser destruction of highly energydemanding photoreceptors 26,33 or from destruction of other retinal neural elements, 34 or from a combination of these factors, including diffusion of oxygen from the anterior chamber in eyes undergoing concomitant vitrectomy and laser treatment. 35 Originally it was suggested that laser panretinal photocoagulation obtained its effect from destruction of ischaemic retina, but in diabetes and after ischaemic retinal vein occlusion, retinal capillary closure leading to retinal ischaemia and hypoxia affects the inner retina while laser is preferentially absorbed, and produces its effects in the RPE and outer retina.…”
Section: Introductionmentioning
confidence: 99%